Defining a role for the subthalamic nucleus within operative theoretical models of subcortical participation in language. Issue 11 (14th November 2003) - Whelan, B-M; Murdoch, B E; Theodoros, D G; Hall, B; Silburn, P
Abstract : Objective: To investigate the effects of bilateral, surgically induced functional inhibition of the subthalamic nucleus (STN) on general language, high level linguistic abilities, and semantic processing skills in a group of patients with Parkinson's disease. Methods: Comprehensive linguistic profiles were obtained up to one month before and three months after bilateral implantation of electrodes in the STN during active deep brain stimulation (DBS) in five subjects with Parkinson's disease (mean age, 63.2 years). Equivalent linguistic profiles were generated over a three month period for a non-surgical control cohort of 16 subjects with Parkinson's disease (NSPD) (mean age, 64.4 years). Education and disease duration were similar in the two groups. Initial assessment and three month follow up performance profiles were compared within subjects by paired t tests. Reliability change indices (RCI), representing clinically significant alterations in performance over time, were calculated for each of the assessment scores achieved by the five STN-DBS cases and the 16 NSPD controls, relative to performance variability within a group of 16 non-neurologically impaired adults (mean age, 61.9 years). Proportions of reliable change were then compared between the STN-DBS and NSPD groups. Results: Paired comparisons within the STN-DBS group showed prolonged postoperative semantic processing reaction times for a range of word types coded for meanings and meaning relatedness. Case by case analyses of reliable change across language assessments and groups revealed differences in proportions of change over time within the STN-DBS and NSPD groups in the domains of high level linguistics and semantic processing. Specifically, when compared with the NSPD group, the STN-DBS group showed a proportionally significant (p<0.05) reliable improvement in postoperative scores achieved on the word test-revised (TWT-R), as well as a reliable decline (p<0.01) in the accuracy of lexical decisions about words with many meanings and a high degree of relatedness between meanings. Conclusions: Bilateral STN-DBS affects certain aspects of linguistic functioning, supporting a potential role for the STN in the mediation of language processes.